Analysis of Factors Related to Incomplete Filling in Medical Recordsat the Sibuhuan General Hospital Poly in 2022 - Anni Kholilah Daulay; Kesaktian Manurung; Frida Liharris Saragih (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
According to WHO, hospitals provide comprehensive curative and preventive services, including quality medical record (MR) management, assessed by completeness, accuracy, timeliness, and legal compliance. This study aimed to analyze factors related to incomplete MR documentation at Sibuhuan Regional Hospital in 2022 using an analytical observational cross-sectional design with 74 health workers as total respondents. Data were analyzed using binary logistic regression. Results showed that supervision, training, and sanctions were significantly related to incomplete MR filling (p<0.05), while knowledge, attitude, and length of work were not (p>0.05). Sanctions were the most dominant factor. It is recommended that the hospital conducts monthly audits to improve MR documentation completeness